Exploring the 'Something for Nothing' Syndrome: Confused Citizens or Free Riders? Evidence from Sweden. (28th November 2012) - Edlund, Jonas; Johansson Sevä, Ingemar
Abstract : This article examines the occurrence of political non‐attitudes in Sweden and identifies the population segment possessing a 'something for nothing' (SFN) mentality regarding social spending. Sweden – often regarded as epitomizing the advanced welfare state – constitutes an analytically interesting case, providing a useful counterpoint to the predominantly American‐based evidence on the subject. It is argued here that national political institutions fundamentally affect the prevalence – and social base – of the SFN segment. To identify SFN sentiments, two question batteries measuring social spending preferences are used. One battery contains 'priced' items emphasizing the cost of public spending, while the other set of 'unpriced' items does not explicitly connect increased public spending with increased taxes. The patterning of attitudes across these items is explored in order to determine whether SFN sentiments are common in the Swedish electorate. The observed attitude patterns are then linked to broader sets of attitudes to the welfare state, testing whether the degree of ideological coherence differs fundamentally between the SFN segment and other groups. The analysis then explores the individual‐level determinants associated with different attitude patterns. The overall results show that: SFN sentiments are not dominant among the Swedish citizenry; the quality of the SFN segment's belief system, in terms of ideological coherence, does not represent a deviant case; and the background characteristics associated with SFN sentiments suggest that members of this segment should rather be viewed as free riders in economically vulnerable positions than ignorant and politically confused citizens.